High-Quality Reference Genome for an Arid-Adapted Mammal, the Banner-Tailed Kangaroo Rat (Dipodomys spectabilis). (13th January 2022) - Harder, Avril M; Walden, Kimberly K O; Marra, Nicholas J; Willoughby, Janna R
Abstract: Kangaroo rats in the genus Dipodomys are found in a variety of habitat types in western North America, including deserts, arid and semiarid grasslands, and scrublands. Many Dipodomys species are experiencing strong population declines due to increasing habitat fragmentation, with two species listed as federally endangered in the United States. The precarious state of many Dipodomys populations, including those occupying extreme environments, make species of this genus valuable subjects for studying the impacts of habitat degradation and fragmentation on population genomic patterns and for characterizing the genomic bases of adaptation to harsh conditions. To facilitate exploration of such questions, we assembled and annotated a reference genome for the banner-tailed kangaroo rat ( Dipodomys spectabilis ) using PacBio HiFi sequencing reads, providing a more contiguous genomic resource than two previously assembled Dipodomys genomes. Using the HiFi data for D. spectabilis and publicly available sequencing data for two other Dipodomys species ( Dipodomys ordii and Dipodomys stephensi ), we demonstrate the utility of this new assembly for studies of congeners by conducting inference of historic effective population sizes ( N e ) and linking these patterns to the species' current extinction risk statuses. The genome assembly presented here will serve as a valuable resource for population and conservation genomic studies of Dipodomys species, comparative genomic research within mammals and rodents, and investigations into genomic adaptation to extreme environments and changing landscapes.